An exploratory study of the social and personal dynamics that deter underserved women from participating in adult education activities. - Abby G. Hall; Joe F. Donaldson (Adult Education Research Conference, 1997)
This study explored the social and personal dynamics that deter underserved women from participating in formal adult education. From a grounded theory perspective, an inductive analysis revealed four integrated categories of deterrents that describe factors leading to nonparticipation (a) preadulthood factors; (b) patterns of nonsupport in adulthood; (c) conventional deterrents; and, (d) lack of "voice" in adulthood.